Morphometric and genetic variations of species composers of nike fish assemblages in Gorontalo Bay Waters, Indonesia - Femy M. Sahami; Rene Charles Kepel; Abdul Hafidz Olii; Silvester Benny Pratasik; Ridwan Lasabuda; Adnan Wantasen; Sitty Ainsyah Habibie (Society for Indonesian Biodiversity, 2020)
Abstract. Sahami FM, Kepel RC, Olii AH, Pratasik SB, Lasabuda R, Wantasen A, Habibie SA. 2020. Morphometric and genetic variations of species composers of nike fish assemblages in Gorontalo Bay Waters, Indonesia. Biodiversitas 21: 4571-4581.  Nike is Gobioidei fish at the post-larval and juvenile stages whose habitat is still in seawater before they migrate to the freshwater, grow up, and spawn to fulfill their life cycle as an amphidromous species. This study aims to identify the species composers of Nike fish in Gorontalo Bay waters based on their morphometric and molecular characters. 2,523 samples were collected from the catches of fishermen during three periods of their appearance in Gorontalo Bay waters from January to March 2019. The samples were grouped based on their similarity of melanophore patterns, and morphometric characters of 10 units were then measured. This study found 20 different groups of melanophore patterns; 15 of them were new melanophore patterns. DNA samples from each group of new melanophore patterns were then isolated for molecular analysis. The morphometric analysis grouped the 20 melanophore patterns into three separate clusters that were confirmed through molecular analysis. The results of Gen Cytochrome Oxidase I (COI) sequences indicate that the new melanophore patterns of Nike fish assemblages consisting of six species; five species in the Gobiidae family (i.e. Sicyopterus parvei, S. cynocephalus, S. longifilis, S. lagocephalus, and Stiphodon semoni) and a species in the Eleotridae family (Belobranchus belobranchus).